Remission of Persistent Negative Symptoms and Psychosocial Consequences by Combined Clozapine and Cariprazine Treatment in a Patient With Long-Standing Treatment-Resistant Schizoaffective Disorder - Bogren, Mats; Soltesz, Monica; Hjorth, Stephan (Frontiers in Psychiatry, 2022)
This patient case report describes a 45-year old white unmarried man with disability pension due to schizoaffective disorder, diagnosed at the age of 24. He lives in an apartment and has housing support. Retrospectively, the patient displayed prodromal markers of a disorder within the schizophrenia spectrum many years before the onset of frank psychosis, indeed since childhood. Over the years several symptoms and signs across schizophrenia domains have been manifest: positive, negative, disorganized, catatonic and affective, among which the negative and affective symptoms and signs were the earliest to appear. While the positive, disorganized and catatonic symptoms responded to treatment – when duly tested and complied with – the negative and affective symptoms have been notoriously difficult to handle. We now report on the successful introduction of cariprazine (CAR) to his ongoing clozapine (CLZ) medication, the result of which has been a near-complete remission of his persistent negative and psychosocial symptom issues. We interpret this remarkable alleviation of the patient’s disease – and concomitant improvement of his quality of life – in terms of neuroreceptor target complementarity between CLZ and CAR, with particular emphasis on the contributions from the D3 and D2 receptor partial agonist components of the latter agent.